POSSIBILITIES OF APPLICATION OF THE ADAPTED SF-36 QUESTIONNAIRE IN THE PEDIATRIC POPULATION - Головкин, Сергей Иванович; Шабалдин, Андрей Владимирович (Mother and Baby in Kuzbass, 2017)
The Sf-36 is a General questionnaire used for the study of quality of life (QOL) in adults. Its use is allowed in adolescents older than 14 years. The youngest age category, some questions posed difficulties, leading to the loss of the main indicators of the objectivity of the study: sensitivity, reliability, validity.The aim of the study – the proposed us version of the Sf-36 questionnaire with some simplifications in matters, without modifying the original ideology, in children of different age groups.Materials and methods. The present study included 42 patients who received surgical treatment about the disease, Legg calve-Perthes (BLK).Results. We obtained significant improvement in QOL depending on the time elapsed since the operation. No issue has caused difficulties from the interviewed patients. The younger age group was uchitany as indicators of self-report and proxy-report.Conclusions. The use of an adapted version of the questionnaire Sf-36 are valid in the pediatric population, enables the objectiveness of the comparison of QOL in children younger and older age categories.
Keywords: Sf-36 questionnaire; quality of life; disease; Legg-calve-Perthes; children